TRACING THE DEVELOPMENT OF DIGITAL CREATIVE SECTORS WORLDWIDE - Fischer, Laura (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
The digital creative industry has gained significant attention and importance in the context of economic and cultural development. With the evolution of digital technology, this industry has become a strategic emerging sector in various regions, contributing to economic growth and cultural innovation. This article examines the trajectory of the digital creative industry in China, tracing its recognition from the Guidelines on the Development of the Yangtze River Delta Region in 2008 to more recent policy initiatives. The "Opinions on Promoting the Highquality Development of the Digital Culture Industry" in 2020 and the "Opinions on Promoting the National Cultural Digital Strategy" have further elevated the status of the digital culture industry, emphasizing the construction of a national cultural big data system. This system aims to integrate traditional Chinese cultural elements with contemporary culture, fostering a unique cultural identity while promoting economic growth. The digital creative industry has become a catalyst for personalized solutions, industrial optimization, and cultural vitality, contributing to a wellrounded development strategy